2013
DOI: 10.1002/etc.2117
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in urban streams and early life stages of pacific coho salmon

Abstract: Abstract-Pesticides are frequently detected in urban streams and are believed to be primarily the result of homeowner use. Although concentrations in most cases are low (<1 mg/L), there is concern that pesticide inputs threaten efforts to restore and enhance salmon habitat. The authors exposed early life stages of coho salmon (Oncorhynchus kisutch) to a pesticide mixture (''cocktail'') representative of those pesticides most frequently reported in urban streams in western Washington State, USA. Life stages wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 32 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…Similarly, earlier life stages including fertilization, hatching success, growth, and survival to 5 wk post swim-up were also unaffected [18]. Prerelease, condition factor, survival, sex ratio, brain AChE activity, and gonado-and hepatosomatic indices were not affected.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Similarly, earlier life stages including fertilization, hatching success, growth, and survival to 5 wk post swim-up were also unaffected [18]. Prerelease, condition factor, survival, sex ratio, brain AChE activity, and gonado-and hepatosomatic indices were not affected.…”
Section: Discussionmentioning
confidence: 88%
“…The cocktail consisted of those pesticides detected in at least 30% of the urban creeks monitored (see Figure 6 in Franz [16]) and included 8 herbicides, including 2 triazines (prometon and simazine), 2 insecticides (both AChE inhibitors), a fungicide, and a breakdown product. None of the endpoints (fertilization, hatching success, growth, and survival to 5 wk post swim-up) were significantly affected [18]. Although results suggested that exposure to the pesticides most frequently detected in urban streams in western Washington does not directly impair early life stages of coho salmon, the extent to which pesticide-exposed fry would suffer reduced survival during smoltification, outmigration, or in the ocean was not reported.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations